Applications of Exopolysaccharides from Microorganisms in Livestock Food Products: A Review - M. Adriansyah; Indri Juliyarsi; Sri Melia; Ade Sukma (Andalasian Livestock, 2026)
Exopolysaccharides (EPS) are biopolymers produced by various microorganisms and belong to the postbiotic group, which has great potential for application in food products, especially livestock products. In recent years, EPS has been increasingly studied owing to its ability to improve the functional properties of food, such as antioxidant, antibacterial, antibiofilm, immunomodulatory, and antitumor activities, as well as its potential as a prebiotic and agent for enhancing probiotic properties, while also improving product technology characteristics. From a food processing technology perspective, EPS play an important role in increasing viscosity, emulsion stability, texture, system stability, and gel formation ability, thereby contributing to improved product quality and stability. The advantage of EPS over live probiotics as a postbiotic lies in its higher stability under processing and storage conditions, making it more applicable in various food matrices. This review focuses on the effects of applying EPS produced by various microorganisms on the quality and functional properties of livestock food products, including milk, meat, eggs, and their processed products. Various research results have shown that the addition of EPS can improve physical stability, improve texture, extend shelf life, and increase functional value. The information provided discusses the influence of EPS produced by various types of microorganisms that have a positive impact on livestock products, such as milk, meat, eggs, and their processed products. Based on the results of this search, this is the first compilation to study the application of EPS in livestock products.